The Engagement of Islamic Religious Education Teachers of Primary Schools in Semarang in Instilling Religious Moderation - Muslih, Muslih; Luthfan, M. Aqil; Abdullah, Rizal Rahman; Setiawan, Andi (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2024)
The study is focused on exploring the engagement of Islamic Religious Education teachers of primary schools in Semarang in instilling religious moderation. It specifically examines aspects such as the teachers’ comprehension of religious moderation, their commitment, their effort and their obstacles in instilling religious moderation. The research was conducted using a descriptive qualitative method, gathering data through interview, questionnaire, observation, and documentation. The findings revealed that while most of the Islamic Religious Education teachers of primary schools in Semarang participating in this study had a good understanding of religious moderation, some teachers still did not understand the concept of religious moderation comprehensively. Although most teachers had a serious commitment and had begun the process of introducing religious moderation to students, a small number of others admitted that they were just about to do so. The teachers made efforts differently in instilling religious moderation to the students, including among others, inserting messages of religious moderation and encouraging student to practice the values of religious moderation both in learning activities in the classroom and outside the classroom. Most teachers encountered obstacles in their struggles to instill religious moderation in students, both internal and external. Internally, the children were noisy and did not focus on listening to the teacher’s explanation. Externally, the time provided by the school is very limited. Based on the findings, this study suggests the need for a serious training to strengthen competency in religious moderation and its implementation for Islamic religious education teachers in elementary schools.